DEMOCRACY, ISLAM, AND RELIGIOUS FREEDOM IN INDONESIA: A SHORT POLITICAL AND RELIGION HISTORY - Hakam, Saiful (JIA (Jurnal Ilmu Agama), 2016)
Indonesia,  even  though  state  gives  a  concession  on  moderate  on  religious  matter,  the phenomena  shows  that  the  radical  Islamic  group  tries  to  intervene  religious  matter  in  Indonesia. Thus  it  might  dangerous  to  manage  the  diversity  that  becomes  national  emblem.  In  this  paper,  I argue  that  democratic  society  should  regulate  and  control  religious  activity.  I  have  two  reasons about  it.  My  reasons  are  based  on  Indonesian  experiences.  First,  the  democratic  society  prevents activities of a majority religion that contain radical political activities and tried to force their values to other citizens.. The Second is the democratic society has a strong idea to protect minority and their religions.